Ethical leadership in sport : what's your ENDgame? - Grange, Pippa (2014 digital library., 2014)
A practical guide on how to navigate the complexities of ethical leadership in sport, recognizing the increasing pressure placed on individuals and organizations in sport to ruthlessly compete to win, and at the same time to be exemplary social role models. Most leaders know right from wrong, but giving voice to your values isn't always straightforward. This book explores how to approach the ethical decisions, dilemmas, and value-based conflicts that emerge for leaders in sports organizations in order to make good choices, drive a sound culture, and reduce the risk of going awry. The approach is twofold: Coaching for the leader on how to make and act on an ethical decision when faced with a dilemma; and an exploration of those deep personal values and beliefs about self and sport that inform how the leader thinks and acts. The book considers ethics in the context of modern sport and highlights the classic ethical traps and cultural slippery slopes to avoid using case studies and examples.